Variation of Water Quality in Ningxia Section of the Yellow River in Recent 5 Years - Jin, Yan; Wang, Xinyuan; Dong, Ya-Ping (Journal of Chemistry, 2022)
The Yellow River is very important for human health and social development in China to require good water quality. This study selected the Ningxia section of the Yellow River as the study area to investigate the water quality variation in 2016–2020. A total of 9 water quality parameters were monitored, and 8 parameters including pH, dissolved oxygen, biological oxygen demand, chemical oxygen demand, total phosphate, fluoride, ammonia-nitrogen, and permanganate index were in the range of Class II standard requirement. Dissolved oxygen concentrations ranged from 7.5 to 9.4 mg/L. However, total nitrogen concentrations in 2018–2020 ranged from 1.87 to 2.8 mg/L to cause the pollution. Both the Nemerow index method and the contamination degree method showed that total nitrogen with high concentration exerted the water pollution. Principal component analysis also proved this. Stricter environmental management strategies for controlling total nitrogen should be taken in the future. The findings provided some useful information for water pollution of the Ningxia section of the Yellow River.